Understanding traceability: its relevance in the adoption of quality and safety measures across the supply chain - de la Torre Dávila, Alondra Yaneth; Haro Navejas, Francisco Javier; Prado Meza, Claudia (Universidad Autónoma de Nuevo León, 2021)
The article is based on a previous case study of a certified papaya producer from Colima which currently implements traceability in its operations. Traceability can be defined as an instrument to respond and avoid risks in the supply chain of a product. For Small and Medium Enterprises (SMEs) the use of traceability can be a competitive advantage, adding value to their products; or either an entry barrier to access to new international markets. The article analyzes the importance of traceability and the adoption of new practices to respond to future market requirements in a competitive globalized environment.